Management of Hypothyroidism in Internal Medicine: Patient Profile and Effects of an Educational Programme in the Cluster-Randomized FADOI TIAMO Study - Brancato, D.; Biondi, B.; Attardo, T. M.; Fierro, A.; Nizzoli, M.; Vettor, R.; Monaco, E.; Romano, R.; Ariete, V.; Usai, C.; Zagarrì, E.; Campanini, M. (Frontiers in Endocrinology, 2022)
Background and aims: There is still limited knowledge regarding clinical profile and appropriateness of treatment for inpatients with hypothyroidism in Internal Medicine (IM) Departments of Italian hospitals. The aim of this study was to evaluate: 1) characteristics of patients, and possible deviations from national and international clinical practice recommendations (CPRs) in evidence-based guidelines (EBGs); 2) improvement of patient management by means of a standardized educational programme (EP). Methods: Nationwide multicentre study, comprising two replications of a retrospective survey (phases 1 and 3), with an intervening EP (phase 2) at half of the centres and no EP at the others. The EP was based on outreach visits. Centres were assigned to the two arms of the study, labelled the training group (TG) and control group (CG) respectively, by cluster randomization. Four EBGs and 39 CPRs provided the basis on which 22 treatment management indicators were identified (7 referring to the time of hospital admission, 15 post-admission). Results: The 21 participating centres recruited 587 hospital inpatients with hypothyroidism (421 females (71.7%), mean age 74.1+14.4 yrs): 318 in phase 1, and 269 in phase 3. The cause of hypothyroidism was unknown in 282 patients (48%). Evaluation at the time of admission identified satisfactory adherence to CPRs (>50%) for 63.6% of the indicators. In the phase 3, TG centres showed significant improvement vs CG in 4 of the 15 post-admission indicators, while 1 out of 15 was significantly worse. Conclusions: The EP based on outreach visits significantly improved some indicators in the management of inpatients with hypothyroidism, with specific reference to appropriateness of TSH dosage and levothyroxine (LT4) treatment modality.